Actual shelf-life testing and development of squid roll. - Pascual, Almira M. (Miagao, Iloilo College of Fisheries, University of the Philippines in the Visayas, 1993)
The recommended steps were followed in the development of squid rolls. New product concepts were generated, evaluated, and refined and the blueprints of a concept (squid rolls) was subsequently created. The squid rolls were then optimized and subjected to actual shelf-life testing. Texture optimization of the product was conducted through variations in the textural characteristics of squid rolls which were subjected to sensory evaluation of quality. On the other hand, the storage stability of the squid rolls was evaluated through the determination of the changes in percent moisture content and Thiobarbituric Acid (TBA) values. in relation to organoleptic changes in squid rolls during storage. Results have shown that the use of skinned squid mantle minced in 4.5/10 cm mincer mesh results to the most preferred texture of squid rolls. Likewise, this treatment yields better quality product in terms of flavor. odor and general acceptability. Further analyses also show that the changes in percent moisture content during storage correlate with the textural changes in squid rolls in terms of moistness and crispiness. However, the TBA test appears not to be an effective technique in determining the quality changes in squid rolls during storage. The shelf-life of the product at -14℃ was not determined at the end of the seven-week storage period. The squid rolls are still acceptable. However,prolonged storage of the product at this abused cold storage temperature results to progressive deterioration of squid rolls.
Thesis
Keywords: Fish Processing